Isu Uyghur dalam Bingkai Media Indonesia: (Analisis Perbandingan Tempo dan Antara) - Betha Dwi Octaviani; Kiki Zakiah; Oji Kurniadi (UPT Publikasi Ilmiah Unisba, 2026)
Abstract. The alleged human rights violations against the Uyghur ethnic minority in Xinjiang, China, have attracted global attention and received extensive coverage in Indonesian media. However, the issue has been framed differently due to variations in editorial orientation and the institutional characteristics of media organizations. This study aims to examine the differences in the framing of the Uyghur issue by Tempo and Antara and to explain how these framings relate to the context of Indonesia–China diplomatic relations. Employing a qualitative approach, this study applies Robert N. Entman’s framing analysis to 20 news articles published by Tempo and 15 by Antara between January 2022 and June 2025. The analysis is complemented by interviews with journalists and media audiences as a form of data triangulation. The findings reveal that Tempo frames the Uyghur issue primarily as a humanitarian concern by emphasizing alleged human rights violations and positioning the victims at the center of the narrative. In contrast, Antara frames the issue within the context of diplomatic relations, the stability of Indonesia–China bilateral ties, and the principle of non-interference. The novelty of this study lies in demonstrating how the institutional characteristics of media organizations shape the implementation of Entman’s framing devices in reporting diplomatically sensitive international issues. The findings extend the application of framing theory by highlighting that institutional characteristics influence the processes of selecting, emphasizing, and interpreting social reality in international communication. Abstrak. Isu dugaan pelanggaran Hak Asasi Manusia (HAM) terhadap etnis Uyghur di Xinjiang, Tiongkok, menjadi perhatian global dan mendapat sorotan media di Indonesia. Namun, pemberitaannya menunjukkan perbedaan perspektif yang dipengaruhi oleh orientasi editorial dan karakter institusional media. Penelitian ini bertujuan menganalisis perbedaan pembingkaian isu Uyghur pada Tempo dan Antara serta menjelaskan kaitannya dengan hubungan diplomatik Indonesia–Tiongkok. Penelitian menggunakan pendekatan kualitatif dengan analisis framing Robert N. Entman terhadap 20 berita Tempo dan 15 berita Antara periode Januari 2022–Juni 2025, yang diperkuat melalui wawancara dengan jurnalis dan pembaca sebagai triangulasi data. Hasil penelitian menunjukkan bahwa Tempo membingkai isu Uyghur sebagai persoalan kemanusiaan yang menekankan dugaan pelanggaran HAM dan menempatkan korban sebagai pusat narasi, sedangkan Antara lebih menempatkannya dalam perspektif hubungan diplomatik, stabilitas bilateral Indonesia–Tiongkok, dan prinsip non-intervensi. Kebaruan penelitian ini terletak pada penjelasan mengenai pengaruh karakter institusional media terhadap implementasi perangkat framing Entman dalam pemberitaan isu internasional. Temuan ini memperluas penerapan teori framing dengan menunjukkan bahwa karakter institusional media memengaruhi proses seleksi, penonjolan, dan interpretasi realitas dalam komunikasi internasional.